Cochlear implantation in children with Autism Spectrum Disorder (ASD): Outcomes and implant fitting characteristics. (October 2021) - Mancini, Patrizia; Mariani, Laura; Nicastri, Maria; Cavicchiolo, Sara; Giallini, Ilaria; Scimemi, Pietro; Zanetti, Diego; Montino, Silvia; Lovo, Elisa; Di Berardino, Federica; Trevisi, Patrizia; Santarelli, Rosamaria
Abstract: Background: Little is known regarding fitting parameters and receptive and expressive language development in cochlear-implanted children (CCI) with profound sensorineural hearing loss (SHL) who are diagnosed with Autism Spectrum Disorder (ASD). The aim of the study was to evaluate a group of ASD CCI users in order to describe their ASD clinical features and CCI outcomes; report on the average electrical charge requirements; and evaluate the possible correlations between electrical and psychophysical outcomes with ASD characteristics. Materials and methods: A multicentre observational study of 22 ASD children implanted in four cochlear implant (CI) centers. Data concerning profound SHL diagnosis, ASD diagnosis, CI timing and CI compliance were collected. Sound Field (SF) was assessed through repeated behavioural measurements. Categories of Auditory Perception (CAP) and Categories of Language (CL) were used to evaluate speech perception and language skills at short (≤2 yrs), medium (5 yrs) and long term (>10 yrs) follow-up. Fitting parameters such as comfortable thresholds, pulse-width (pw, μsec) and clinical units converted into units of charge/phase were collected. The diagnosis of ASD was acquired by the referral neuropsychiatric department and severity was assessed through the Diagnostic and Statistical Manual of Mental Disorders (DSM-V) and the Childhood Autism Rating Scale (CARS). Results: At the final follow-up session the median SF threshold for CI outcomes was 30 dB HL (min 15 – max 60). CAP score was extremely variable: 45.5% showed no improvement over time and only 22% of children reached CAP scores of 5–7. CL 45.5% showed no improvement over time and score was 1–2 in the majority of ASD children (72.7%), while only 18.2% reached the highest level of language skills. There were no statistically significant differences at each follow-up between subjects with or without comorbidities. CAP and CL were inversely correlated with DSM-V A and B domains, corresponding to lower speech and language scores in children with more severe ASD symptoms, and maintained their correlation at mid and long follow-ups whilst controlling for age at CI. Electrical charge requirements did not correlate with SF or age at implant but did inversely correlate with ASD severity. With regards to CI compliance: only 13.6% children (3) with severe DSM-V A/B levels and CARS score were partial/intermittent users. Conclusion: The present study is a targeted contribution to the current literature to support clinical procedures for CI fitting and audiological follow-up in children with ASD. The findings indicate that the outcomes of CI use and the fitting procedures are both influenced by the severity of the ASD symptoms rather than the demographic variables or associated disorders.